2007
DOI: 10.1002/pon.1200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cancer on Moslem patients in Morocco

Abstract: One thousand and six hundred patients (median age 49 years) were approached; 41% females and 74% from rural areas. There was a high rate of illiteracy (38%) and only 7% had higher education. Seventeen per cent were divorced, among whom 41% were divorced after diagnosis of cancer. Eighty-seven per cent had no medical insurance. All were Muslims; 49% practising believers and 51% non-practising. In the first group cancer represented a divine test that permitted acceptance of the disease. In the second group of 'n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 9 publications
2
33
1
Order By: Relevance
“…The Persian version of the FACIT-Sp scale is an important and valid tool for the clinical assessment of, and research into, the spiritual well-being of Muslim Iranian and Farsi-speaking (Iran, Afghanistan, and Tajikistan) patients in other regions of the world who are coping with cancer. This result was also observed in another validation study among Iranian patients,70,71 a Jordanian population,16 a sample from Saudi Arabia,25 a sample from Morocco2729 and among Japanese patients 72. This indicates that cultural issues should be considered when applying a standard questionnaire in a heterogenous population context.…”
Section: Complementary and Alternative Medicinesupporting
confidence: 67%
See 1 more Smart Citation
“…The Persian version of the FACIT-Sp scale is an important and valid tool for the clinical assessment of, and research into, the spiritual well-being of Muslim Iranian and Farsi-speaking (Iran, Afghanistan, and Tajikistan) patients in other regions of the world who are coping with cancer. This result was also observed in another validation study among Iranian patients,70,71 a Jordanian population,16 a sample from Saudi Arabia,25 a sample from Morocco2729 and among Japanese patients 72. This indicates that cultural issues should be considered when applying a standard questionnaire in a heterogenous population context.…”
Section: Complementary and Alternative Medicinesupporting
confidence: 67%
“…In one report, 695 participants (136 cancer patients, 161 informal careers, and 398 health care professionals) were recruited from oncology centers in four major regions of Saudi Arabia 26. The results of a large set of data on the psycho-social and religious impact of cancer diagnoses are reported by three independent research workers from Morocco 2729. A qualitative study demonstrated that Malaysian Muslim women with advanced breast cancer look to their Islamic beliefs for peace and strength to deal with the illness 30.…”
Section: The Context Of Middle Eastern Spiritual Therapymentioning
confidence: 99%
“…Patients only refused life-sustaining treatments in cases where the patient was suffering from poor family relationships, pain or depression. Errihani et al (2008) found that patients with cancer who were not practicing Muslims (49%) often felt guilty, while active believers commonly accepted cancer as a divine test [51]. …”
Section: Resultsmentioning
confidence: 99%
“…Through prayer and meditation, many Muslims seek support and help from Allah during suffering and illness (Errihani et al . ). Moreover, many Muslim patients view their disease as a part of life, a test from Allah, and a way of atonement for their sins.…”
Section: Introductionmentioning
confidence: 97%